Potential of Zakat as an Alternative Source of Financing for MSMEs: A Review of the Perspective of Islamic Economics - Ramadhan SY, Taufik; Aidil Alfin; Eli Febriani; Indra Saputra (Proceeding of The International Conference on Economics and Business, 2024)
This study discusses the potential of zakat as an alternative source of financing for Micro, Small, and Medium Enterprises (MSMEs) from a sharia economic perspective. Zakat not only functions as a religious obligation, but also an economic instrument that supports community empowerment, especially MSME actors. In the Indonesian context, the MSME sector plays a strategic role in economic growth, but often faces financing constraints from formal financial institutions. This study examines the extent to which productive zakat can support MSMEs through the distribution of business capital, skills training, and capacity development. Based on library research methods, it was found that although zakat has great potential to strengthen MSMEs, its implementation still faces challenges, such as less transparent management and less than optimal coordination between stakeholders. This study recommends more professional zakat management, increased coordination between zakat institutions and the government, and training for zakat recipients so that its impact is more sustainable. By optimizing the use of zakat, it is hoped that MSMEs can develop inclusively, while supporting national economic growth.